(3RGO GdeSjQs - (3YHO GdQMef Hf Ydj Hf eMeO GdLhRj GdbQTj GdHZOGOj, CHh GdaQL, GHf GdLhRj , J (B597 (3g` s ((3GHh MGeO eMeO Hf YHO GdNGdb Hf CHj gGTe GdcQLi s)
(3ChdgG (B:s
(3ShQI GdCfYGe aVd ai fRhdgG Qhi eLGgO Yf GHf YHGS Cf GdCfYGe s
(3BNQgG (B:s
(3bGd GdRLGL eYfi GdBjI CYHO QHc GHOkG hGdKGfi Cfg GdMb GdPi dGQjH ajg ef fUQc Ydi CYOGFc McGg GdeGhQOi BNQ GdLRA GdKGfi ef cJGH RGO GdeSjQ ai Yde GdJaSjQ s
(3ChQGb ef Chdg hBNQgs
(3cJH GdeNWhW Hbde ajg VHWs
(3bQf GdfSN (B:s
(3GdbQf GdSGHYs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B3 - (3U (B316 ; (3eYLe GdeDdajf ; YeQ QVG cMGdI (B, (3J (B1408 (3g` (B/ 1987 (3e(B: (3L (B5 - (3U (B157 ; (3gOjI GdYGQajf ddHZOGOi(B: (3L (B1 - (3U (B520s
Keywords: (3GdJaSjQ hYdhe GdbQBfs